Трансформація економіки під впливом мережевих технологій - Мороз, М. Ю. (ХНУРЕ, 2024)
This paper explores the profound transformation of the economy catalyzed by the pervasive influence of network technologies. Through an interdisciplinary lens, it investigates the multifaceted impact of network technologies such as the internet, blockchain, and artificial intelligence on economic structures, business models, and societal dynamics. Additionally, it examines the challenges and opportunities posed by the integration of network technologies, including issues related to cybersecurity, digital inclusion, and regulatory frameworks. Ultimately, this research contributes to a deeper understanding of how network technologies are reshaping the economic landscape and shaping the future of global commerce
Keywords: трансформація економіки; мережеві технології